Modification of the multiphase shape memory composites with functionalized graphene nanoplatelets: enhancement of thermomechanical and interfacial properties. (June 2022) - Tiwari, N.; Shaikh, A.A.; Malek, N.I.
Abstract: Ameliorating the mechanical and thermomechanical properties of the shape memory polymers (SMPs) make them an important class of materials for new-age applications ranging from aerospace, electronics, and marine. To show the more recent attempts proof-of-concept in designing the SMPs with higher mechanical and thermomechanical properties, herein we had designed the multiscale shape memory hybrid composites (SMHCs) having known composition of functionalized graphene nanoplatelets (fGNPs) through dispersing the fGNPs uniformly using ultrasonication in shape memory epoxy polymer. Subsequently, hybrid composites were prepared through impregnation of carbon fiber in the fGNP ∼ epoxy solution. Mechanical and thermomechanical characterizations were performed to evaluate the effect of the fGNPs within the SMHC. Significant improvement in the mechanical and thermomechanical properties were achieved in the SMHC with amine functionalized fGNP compared with the carboxy functionalized fGNP and non-functionalized epoxy polymer. Compared with the unmodified carbon fiber reinforced polymer composites, SMHC with 0.4 and 0.6 wt% amine fGNP improved by 19.7% and 33.2%, whereas 5.9% and 17.4% by carboxyl fGNP. Morphological study indicated the improvement of wettability of carbon fiber and interfacial bonding between the fiber and matrix. The recovery of the modified polymer composites into the original shape primarily occurred due to the gradual release of internal energy harnessed in the frozen and active phase of the polymer network. Due to the incorporation of nanofillers, the molecular kinetic energy of the reversible active phase increases, which intensifies the micro-Brownian motion. Thereby, the recovery stage was achieved due to the return of the frozen phase to the disoriented entropy condition. The addition of nanoparticles increases the cross-linking, which in turn increases the volume of the frozen phase. Hence, higher volume of frozen phase would hamper the recovery of the samples in its original shape, resulting in the lower shape fixity. However, the shape memory parameters of shape fixity and shape recovery evaluated with the heat activation bending did not degraded significantly and remained ∼95 ± 2% and ∼96 ± 1%, respectively. Graphical abstract: Image 1 Highlights: Modification of matrix with amine and carboxyl functionalized graphene through ultrasonication and shear mixing. 33.2% improvement in elastic modulus due to the incorporation of functional groups, respectively. No adverse effect on the shape memory properties of the composites with shape fixity and shape recovery of 95 and 96%, respectively.